2021
DOI: 10.1108/dprg-11-2020-0164
|View full text |Cite
|
Sign up to set email alerts
|

HPC in business: the impact of corporate digital responsibility on building digital trust and responsible corporate digital governance

Abstract: Purpose The implementation of high performance computing (HPC) in business (especially small and medium-sized enterprises) is accompanied with mistrust to a certain extent, which has imposed the need for building of digital trust (DTrust) among stakeholders. The purpose of the present paper is to find out the ways on how to build and maintain such trust. Design/methodology/approach Analysis and critical reflection on previous research dealing with phenomena of digital transformation (DT), HPC, corporate digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 26 publications
(27 reference statements)
0
16
0
Order By: Relevance
“…They concluded that this may lead to cross-company disruption, entailing organisational restructuring, new staff competencies and re-training, and the redesign of data management and communication processes. The research of Jelovac et al [11] similarly examined the impact of CDR on building digital trust and responsible corporate governance in companies. They concluded that "the best response to building and maintaining trust is, in our opinion, the building of a new modern business and organizational CDR culture" (p. 494).…”
Section: Relevant Literaturementioning
confidence: 99%
“…They concluded that this may lead to cross-company disruption, entailing organisational restructuring, new staff competencies and re-training, and the redesign of data management and communication processes. The research of Jelovac et al [11] similarly examined the impact of CDR on building digital trust and responsible corporate governance in companies. They concluded that "the best response to building and maintaining trust is, in our opinion, the building of a new modern business and organizational CDR culture" (p. 494).…”
Section: Relevant Literaturementioning
confidence: 99%
“…Drawing on these perspectives, our paper proposes a comprehensive and holistic definition of CDR as the practices, policies, and governance structures organizations adopt during their digital transformation (Van der Merwe & Al Achkar, 2022). At the core of CDR lies the cultivation of responsible digital practices, the establishment of robust enforcement mechanisms, the pursuit of sustainable growth and development, and the fostering of trust within the digital ecosystem (Jelovac et al, 2022). CDR must encompass the intricate interplay between digitalization, society, and the environment, recognizing its profound impact on individuals, communities, and states.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…This approach ensures compliance with legal and ethical standards and demonstrates the company's commitment to the well-being of society and the environment. Embracing CDR can enhance the company's reputation, foster stakeholder trust, and positively impact the organization and the broader community (Jelovac et al, 2022). Thus, CDR represents an integrative and forward-thinking approach to corporate responsibility in the digital age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digitalization should provide the market with modern technological solutions, using which the company will provide itself with an advantage in the rate of reducing specific operating and investment costs, optimize innovative development, infrastructure maintaining and the structure of technological process management. Analyzing numerous works devoted to this issue [1][2][3][4][5][6][7][8][9][10], and pilot digitalization projects, in the activities of modern companies, it can be identified several main areas that will be «digitized» and a description for them were give (Table 2). ensuring transparency, simplicity and efficiency of interaction with the authorities.…”
Section: Corporate Models Of Digital Transformation Of Economic Secur...mentioning
confidence: 99%